Analysis of Urea, Creatinine, and Platelet Indices in Hypertensive Patients - Ratna Delima Hutapea; Yuyun Widaningsih; Fitriani Mangarengi; Darwati Muhadi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Hypertension may lead to complications of kidneys and blood vessels. Measurement of urea, creatinine, and platelet indices can be markers of renal function and endothelial dysfunction in hypertensive patients. This study aimed to analyze the profile and correlation between renal function parameters such as urea and creatinine and platelet indices (MPV, PDW, and PCT) with blood pressure in hypertensive patients. One hundred and thirty-third hypertensive patients treated at Wahidin Sudirohusodo Hospital from April to July 2019 were involved in this cross-sectional study. Researchers collected demographic data, blood pressure degrees (based on ESC 2018), systolic and diastolic blood pressure, and urea, creatinine, and platelet index value (MPV, PDW, and PCT) data from the medical record. Descriptive analysis, Spearman test, Fisher exact test, and Kruskal-Wallis test were used confidence interval of 95%. A total of 133 participants were involved in this research. There were significant difference between the mean age (p=0.023), MPV (p=0.032), and PCT (p=0.019) to the degree of hypertension, while gender (p=0.185), urea (p=0.106), creatinine (p=0.498), platelet (p=0.094) and PDW (0.826) showed no significant difference. The bivariate correlation test showed that urea (rs= -0.232 p=0.007) and creatinine (rs= -0.180 p=0.038) had a positive correlation with systolic blood pressure. Platelets index, MPV (rs=0.285 p=0.001), and PDW (rs=0.179) were positively correlated to systolic blood pressure. Also, urea levels and creatinine were positively correlated with MPV value. There was an increase in MPV along with the increase of urea, creatinine. An increase in MPV could be a predictor of endothelial damage and the risk of atherothrombosis.